A produção videográfica dos Guarani : entre o político e a arte - Wolf, Ivanirce Gomes (2019)
This dissertation investigates audiovisual production of Guarani indigenous filmmakers trying to understand in what these videos differ from the non-indigenous film production. The positioning of the indigenous people as filmmakers began in the pioneer pr